Energization of the Ring Current by Substorms. Issue 10 (8th October 2018) - Sandhu, J. K.; Rae, I. J.; Freeman, M. P.; Forsyth, C.; Gkioulidou, M.; Reeves, G. D.; Spence, H. E.; Jackman, C. M.; Lam, M. M.
Abstract: The substorm process releases large amounts of energy into the magnetospheric system, although where the energy is transferred to and how it is partitioned remains an open question. In this study, we address whether the substorm process contributes a significant amount of energy to the ring current. The ring current is a highly variable region, and understanding the energization processes provides valuable insight into how substorm‐ring current coupling may contribute to the generation of storm conditions and provide a source of energy for wave driving. In order to quantify the energy input into the ring current during the substorm process, we analyze Radiation Belt Storm Probes Ion Composition Experiment and Helium Oxygen Proton Electron ion flux measurements for H +, O +, and He + . The energy content of the ring current is estimated and binned spatially for L and magnetic local time. The results are combined with an independently derived substorm event list to perform a statistical analysis of variations in the ring current energy content with substorm phase. We show that the ring current energy is significantly higher in the expansion phase compared to the growth phase, with the energy enhancement persisting into the substorm recovery phase. The characteristics of the energy enhancement suggest the injection of energized ions from the tail plasma sheet following substorm onset. The local time variations indicate a loss of energetic H + ions in the afternoon sector, likely due to wave‐particle interactions. Overall, we find that the average energy input into the ring current is ∼9% of the previously reported energy released during substorms. Plain Language Summary: The Earth's near‐space environment is populated by energetic charged particles, whose motion is largely controlled by the global geomagnetic field. This region, known as the magnetosphere, is highly dynamic and variable, strongly coupled to the solar wind (a continuous stream of charged particles outflowing from the Sun). At times, the Earth's magnetic field can become highly distorted and release a large amount of energy into the magnetospheric system. This process is termed a substorm, and the release of energy has significant consequences for the structure of the region and the characteristics of the plasma within it. The amount of energy that is transferred to the magnetospheric particle population remains to be fully understood. In this study, we use spacecraft measurements of highly energetic particles observed by the Van Allen Probes between 2012 and 2017. Using a statistical approach, we quantify the magnitude of the energy input into the particle population due to a typical substorm. Furthermore, we investigate the location of the energy enhancements, providing an insight into how energy is transported throughout the magnetospheric system. Key Points: This study explored the spatial variations of the average ring current energy content for H+, O+, and He+ ions The ring current energy content increases following substorm onset with strong spatial dependences Approximately 9% of the energy released in a typical substorm is transferred to the ring current